When Leptin Is Not There: A Review of What Nonsyndromic Monogenic Obesity Cases Tell Us and the Benefits of Exogenous Leptin - Salum, Kaio Cezar Rodrigues; Rolando, Jônatas de Mendonça; Zembrzuski, Verônica Marques; Carneiro, João Regis Ivar; Mello, Cicero Brasileiro; Maya-Monteiro, Clarissa Menezes; Bozza, Patrícia Torres; Kohlrausch, Fabiana Barzotto; da Fonseca, Ana Carolina Proença (Frontiers in Endocrinology, 2021)
Obesity is a pandemic condition of complex etiology, resulting from the increasing exposition to obesogenic environmental factors combined with genetic susceptibility. In the past two decades, advances in genetic research identified variants of the leptin-melanocortin pathway coding for genes, which are related to the potentiation of satiety and hunger, immune system, and fertility. Here, we review cases of congenital leptin deficiency and the possible beneficial effects of leptin replacement therapy. In summary, the cases presented here show clinical phenotypes of disrupted bodily energy homeostasis, biochemical and hormonal disorders, and abnormal immune response. Some phenotypes can be partially reversed by exogenous administration of leptin. With this review, we aim to contribute to the understanding of leptin gene mutations as targets for obesity diagnostics and treatment strategies.